Deep Brain Stimulation Target Selection in Co-Morbid Essential Tremor and Parkinson's Disease. (8th July 2020) - Wadhwa, Anant; Schaefer, Sara; Gerrard, Jason; Deeb, Wissam; Okun, Michael S.; Patel, Amar
Clinical Vignette: A 64-year-old man with essential tremor (ET) and Parkinson's disease (PD) presented with medically refractory, large amplitude, debilitating rest and action tremor in his extremities. Clinical Dilemma: Ventral intermediate nucleus of the thalamus (VIM) deep brain stimulation (DBS) improves tremor in ET and PD but does not ameliorate bradykinesia and rigidity in PD. The comparative efficacy of subthalamic nucleus (STN) DBS in managing action ET tremor remains unclear. Clinical Solution: Bilateral STN was selected as the DBS target. Moderate improvement in rest tremor and mild improvement in action tremor were noted following initial programming. Gap In Knowledge: There are no head-to-head trials to guide DBS target selection in patients with both ET and PD. Current evidence is limited to a few small head-to-head trials that have demonstrated equivalent efficacy in tremor reduction in PD patients using VIM as DBS target and in ET patients using STN. Expert Commentary: Due to limited evidence, DBS treatment of complex cases, such as combined Parkinson's disease and essential tremor, remains based on expert consensus at each institution. Further multi-approach efforts, using imaging, electrophysiologic, and animal data, will be needed to answer the identified gap in knowledge. Highlights: There is limited evidence to guide deep brain target selection in patients with essential tremor and Parkinson's disease. We review existing literature and propose strategies to manage tremor in these patients.